Exploring the Ethical Dimensions of Mandatory Immunization Discourse for School Attendance in Indonesia - Marpaung, Yosi Marin (Center for Health Policy and Management, 2024)
Mandating complete vaccination for school attendance is still in the discourse for the future policy in Indonesia. Like any other policy, this discourse needs to be given an open space to be looked in a critical point view of ethic. This article critically examines the ethical dimensions surrounding the discourse of implementing mandatory immunization for school attendance in Indonesia, employing a multi-faceted ethical analysis. A case study utilizing moral reasoning through the lenses of utilitarianism, Kantian ethics, virtue ethics, and principlism was employed. From a utilitarian standpoint, mandatory vaccination is ethically justifiable, emphasizing its potential to yield substantial health benefits for society, reduce healthcare spending, and contribute to economic growth. The straightforward nature of this intervention, unlike other complex public health measures, makes it an appealing strategy for increasing vaccination coverage. However, Kantian, non-maleficence, and autonomy perspectives introduces ethical complexities, as mandatory immunization may be perceived as infringing upon individual beliefs and personal choice. The article advocates for open and honest discussions, understanding religious perspectives, and fostering trust in governmental decision-making to address these concerns. Virtue ethics are explored to underscore the importance of cultivating social responsibility in the success of public health measures. It further emphasizes the need for a just implementation of the policy, treating the specific needs of regions. In conclusion, the article posits that while the benefits of mandatory immunization are substantial, ethical considerations demand a delicate balance between promoting public health goals and respecting individual freedom. It suggests that achieving immunization targets necessitates a comprehensive approach, including respecting individual choices, building trust, widespread education on vaccine benefits and risks, and ensuring sustainable financing and vaccine procurement across all segments of Indonesia.